Pengaruh Kualitas Pelayanan Dan Kinerja Karyawan Terhadap Kepuasan Nasabah PT. Bank DKI Tbk Divisi Cash Pooling Center - Rahmawati, Ratih; Siska, Elmira (Jurnal Bintang Manajemen, 2024)
In the problems that have occurred, we can see the customer's insatisfaction with the services provided by the bank to the customer in providing services. Of course with this will result in a decrease in many users of the company's services. The aim of this research is to determine the impact of the quality of service and employee performance on customer satisfaction of PT. Bank DKI Tbk Division Cash Pooling Center. The researchers used statistical quantitative motodes. The data was collected using a questionnaire distributed to 40 respondents. Data analysis using data quality test instrument, classical assumption test, double linear regression analysis, hypothesis test and determination coefficient test. The results of the study concluded that partially the service quality variable has no influence on customer satisfaction (the test result is 1,062 < t table 2,026) and on employee performance has an influence over customer satisfying (t count 3,782 > t Table 2,026. Simultaneously, the quality of service and employees performance variables have an impact on customer satisfaction (F count obtained is 14,158 > F table 3,24).